Effects of reduced nitrogen and suitable soil moisture on wheat (Triticum aestivum L.) rhizosphere soil microbiological, biochemical properties and yield in the Huanghuai Plain, China - Su-mei ZHOU; Man ZHANG; Ke-ke ZHANG; Xi-wen YANG; De-xian HE; Jun YIN; Chen-yang WANG (Journal of Integrative Agriculture, 2020)
Soil management practices affect rhizosphere microorganisms and enzyme activities, which in turn influence soil ecosystem processes. The objective of this study was to explore the effects of different nitrogen application rates on wheat (Triticum aestivum L.) rhizosphere soil microorganisms and enzyme activities, and their temporal variations in relation to soil fertility under supplemental irrigation conditions in a fluvo-aquic region. For this, we established a split-plot experiment for two consecutive years (2014–2015 and 2015–2016) in the field with three levels of soil moisture: water deficit to no irrigation (W1), medium irrigation to (70±5)% of soil relative moisture after jointing stage (W2), and adequate irrigation to (80±5)% of soil relative moisture after jointing stage (W3); and three levels of nitrogen: 0 kg ha−1 (N1), 195 kg ha−1 (N2) and 270 kg ha−1 (N3). Results showed that irrigation and nitrogen application significantly increased rhizosphere microorganisms and enzyme activities. Soil microbiological properties showed different trends in response to N level; the highest values of bacteria, protease, catalase and phosphatase appeared in N2, while the highest levels of actinobacteria, fungi and urease were observed in N3. In addition, these items performed best under medium irrigation (W2) relative to W1 and W3; particularly the maximum microorganism (bacteria, actinobacteria and fungi) amounts appeared at W2, 5.37×107 and 6.35×107 CFUs g−1 higher than those at W3 in 2014–2015 and 2015–2016, respectively; and these changes were similar in both growing seasons. Microbe-related parameters fluctuated over time but their seasonality did not hamper the irrigation and fertilization-induced effects. Further, the highest grain yields of 13 309.2 and 12 885.7 kg ha−1 were both obtained at W2N2 in 2014–2015 and 2015–2016, respectively. The selected properties, soil microorganisms and enzymes, were significantly correlated with wheat yield and proved to be valuable indicators of soil quality. These results clearly demonstrated that the combined treatment (W2N2) significantly improved soil microbiological properties, soil fertility and wheat yield on the Huanghuai Plain, China.